Successive reactivation of older structures under variable heat flow conditions evidenced by K-Ar fault gouge dating in Sierra de Ambato, northern Argentine broken foreland - Nobile, Julieta (2015)
The Argentine broken foreland has been the subject of continuous research to determine the uplift and exhumation history of the region. High-elevation mountains are the result of N-S reverse faults that disrupted a W-E Miocene Andean foreland basin. In the Sierra de Ambato (northern Argentine broken foreland) the reverse faults offset Neogene sedimentary rocks (Aconquija Fm., ~9 Ma) and affect the basement comprising Paleozoic metamorphic rocks that have been dated at ~477-470 Ma. In order to establish a chronology of these faults affecting the previous continuous basin we date the formation age of clay minerals associated with fault gouge using the K-Ar dating technique. Clay mineral formation is a fundamental process in the evolution of faults under the brittle regime (<<300 °C). K-Ar ages (9 fractions from 3 samples collected along a transect in the Sierra de Ambato) vary from Late Devonian to Late Triassic (~360-220 Ma). This age distribution can be explained by a long lasting brittle deformation history with a minimum age of ~360 Ma and a last clay minerals forming event at ~220 Ma. Moreover, given the progression of apparent ages decreasing from coarse to fine size fractions (~360-311 Ma for 2-1 μm grain size fraction, ~326-286 Ma for 1-0.2 μm and ~291-219 Ma of <0.2 μm), we modeled discrete deformation events at ~417 Ma (ending of the Famatinian cycle), ~317-326 Ma (end of Gondwanic orogeny), and ~194-279 Ma (Early Permian - Jurassic deformation). According to our data, the Neogene reactivation would not have affected the K-Ar system neither generated a significant clay minerals crystallization in the fault gouge, although an exhumation of more than 2 Km is recorded in this period from stratigraphic data.